2019
DOI: 10.1021/acs.jnatprod.8b00938
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids from the Endophytic Fungus Rhinocladiella similis

Abstract: Ten new sesquiterpenoid derivatives, rhinomilisins A−J (1−10), along with six known analogues (11−16), were isolated from the mangrove-derived endophytic fungus Rhinocladiella similis. The structures of the new compounds were elucidated by their NMR and MS data, while the absolute configuration of 3 and 6 was determined by X-ray crystallographic analysis and Mosher's method, respectively. All isolated compounds (1−16) were evaluated for their cytotoxicity against the mouse lymphoma cell line L5178Y, and compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 23 publications
2
27
0
1
Order By: Relevance
“…This assignment was identical with the data in the literature. [10] The HR-MS and NMR data analyses showed that compound 4 shared the same planar structure of rhinomilisin E. [6] Liu et al reported the determination of the planar structure and relative configurations of this compound, however, its absolute configuration still remained unresolved. With this current work, we determined the absolute configurations of the four chiral centers in 4 as (1R,6S,7R,10S) by comparison the experimental with the calculated ECD spectra (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This assignment was identical with the data in the literature. [10] The HR-MS and NMR data analyses showed that compound 4 shared the same planar structure of rhinomilisin E. [6] Liu et al reported the determination of the planar structure and relative configurations of this compound, however, its absolute configuration still remained unresolved. With this current work, we determined the absolute configurations of the four chiral centers in 4 as (1R,6S,7R,10S) by comparison the experimental with the calculated ECD spectra (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Compound 6 was identified as rhinomilisin G by compairing the MS and NMR data with the literature. [6] However, the absolute configuration of rhinomilisin G remained undetermined. Once the relative configuration of 6 was revealed as the same of rhinomilisin G by detailed analysis of the ROESY data (Figure 3), we measured the ECD spectrum for 6 in MeCN.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations